Rigorous solution by analytical regularization method to the problem of 2D E-polarized wave diffraction by a set of PEC surfaces - Yiğit, Hüseyin; Dikmen, Fatih; Suvorova, Olga; Tuchkin, Yury Alexanderovich (My University, 2009)
The analytical regularization method is applied to the problem of 2D E-Polarized wave diffraction by perfectly conductive surfaces consisting of a set of closed and unclosed surfaces. The electromagnetic boundary value problem is reduced to the infinite algebraic system of the second kind which in principal can be solved with any predetermined accuracy by means of truncation procedure. Numerical results, including condition number behavior, current density, and field's space distribution for obstacles are presented. ©2009 IEEE. © 2009 Elsevier B.V., All rights reserved.
2009 Computational Electromagnetics International Workshop, CEM 2009 -- Izmir -- 78006
Keywords: Algebraic system; Analytical regularization; Condition numbers; Conductive surfaces; E-polarized waves; Electromagnetic boundary value problems; Numerical results; Rigorous solution; Space distribution; Truncation procedure; Differential equations; Diffraction; Diffraction gratings; Dynamic loads; Electromagnetism; Number theory; Two dimensional